1974
DOI: 10.1136/gut.15.11.889
|View full text |Cite
|
Sign up to set email alerts
|

The role of secretin in the inhibition of gastric secretion by intraduodenal acid

Abstract: SUMMARY The effect of intraduodenal acid on pentagastrin-stimulated gastric secretion has been investigated in 12 normal subjects and 23 patients with chronic duodenal ulceration. Plasma secretin levels were monitored during each test using a highly sensitive radioimmunoassay.Significant inhibition of gastric secretion occurred in the normal subjects and duodenal ulcer patients. A significant rise in plasma secretin was observed in both groups after intraduodenal acid though there was a complete lack of correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…All the published work in man and cats has employed doses of GIH secretin in excess of 1 c.u./kg or 2 c.u./kg hr which are likely to exceed the amount of secretin released during feeding (Vagne, Descos & Martin, 1969;Meyer et at. 1970;Ward & Bloom, 1974 (Braganza et al 1975a). We have shown previously that acid stimulants which produce little or no pepsin enhance the peptic response to a dose of secretin, itself below the threshold of peptic stimulation by increasing gastric mucosal blood flow (Reed & Sanders, 1971;Reed, Smy, Venables & Harris, 1973) and thus causing a 2-4-fold increase in the concentration of secretin in the peptic cell (Braganza et al 1975a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the published work in man and cats has employed doses of GIH secretin in excess of 1 c.u./kg or 2 c.u./kg hr which are likely to exceed the amount of secretin released during feeding (Vagne, Descos & Martin, 1969;Meyer et at. 1970;Ward & Bloom, 1974 (Braganza et al 1975a). We have shown previously that acid stimulants which produce little or no pepsin enhance the peptic response to a dose of secretin, itself below the threshold of peptic stimulation by increasing gastric mucosal blood flow (Reed & Sanders, 1971;Reed, Smy, Venables & Harris, 1973) and thus causing a 2-4-fold increase in the concentration of secretin in the peptic cell (Braganza et al 1975a).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of secretin released during feeding maybe less than theequivalent ofGIH secretin 0 5 c.u./kg hr both in dog (Meyer, Way & Grossman, 1970) and in man (Ward & Bloom, 1974), a dose which initiates pancreatic secretion in the anaesthetized cat. 74 J. M. BRAGANZA, A. C. C. GIBBS AND H. T. HOWAT Experiments in which four acid stimulants were administered singly and together with Boots secretin 4 Crick-Harper-Raper u./kg hr which is equivalent to GIH secretin 1 c.u./kg hr as a pancreatic stimulant (Braganza, Howat & Kay, 1975b), provided an opportunity to examine the influence of a small dose of secretin on the acid secretion in cats.…”
Section: Introductionmentioning
confidence: 94%
“…Radioimmunoassays of circulating secretin have also suggested that the amounts released during acid stimulation were much smaller than the circulating levels apparently necessary to induce an inhibition by the exogenous hormone, at least of gastric secretion (28). On the other hand, truncal, selective and highly selective vagotomy had no effect on secretin release in man (29).…”
Section: Discussionmentioning
confidence: 99%
“…As far as the secretion is concerned, recent studies have supported the importance of a normal vagal supply in the effects of acid (26,28) and hyperosmolar agents (27). Clas sical studies of gastric motility report discordant results, some authors claiming that vagotomy suppresses the effects of acid (19,23) and others indicating that only coeliac ganglionectomy can alter acid inhibition (21).…”
Section: Introductionmentioning
confidence: 99%
“…Both groups agree that circulating secretin increases following intraduodenal instillation of acid. In patients with a duodenal ulcer this procedure produces only half the usual response indicating that reduction of the gastric inhibitory action of this hormone and reduced secretion of pancreatic bicarbonate may have an important role in preventing healing of such an ulcer (Ward and Bloom, 1974). Whether the failure is primary or secondary is unclear and the gastric inhibitory roles of other hormones in duodenal ulceration is not established.…”
Section: Tests Of Exocrine Pancreatic Function 79mentioning
confidence: 99%